Pengaruh Media Powtoon dalam Pembelajaran Sains Berbasis Masalah Terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Aidiyana Auva; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to analyzed the influence of Powtoon media in problem based natural sciences learning on the critical thinking abilities of fifth grade elementary school students in the aspects of interpretation, analysis and inference. The research design used was Quasi-Experimental research with a Pretest-Posttest Control Group design. The type used is quantitative data non-test instruments in the form of expert validation sheets and tests in the form of critical thinking ability tests. Based on the results of the studied, it can be concluded that powtoon media in problem based natural sciences learned can improve critical thinking skills in aspects of interpretation. The average posttest in the control class was (76.36), the experimental class was (87.00). The percentage of N-Gain calculation is (81%) with large categories. The average posttest in the control class was (73.64), the experimental class was (85.00). The percentage of N-Gain value is (81%) with large categories. The used of powtoon media in problem based natural sciences learned has a significant effect on critical thinking skills in inferential aspects. The average posttest in the control class was (74.55), the experimental class was (86.00). The N-Gain value is (0.91) if the percentage is (81%) with a large category. The relationship between critical thinking skills in aspects of interpretation and analysis together with inference has a positive relationship with a very strong level of relationship with coefficiency (0.92). Aspects of analysis and inference with coefficient (0.59). Aspects of interpretation and analysis have coefficient (0.80). The used of powtoon media in problem based natural science learned can improve critical thinking skills in aspects of interpretation, analysis, and interpretation in large categories and has a positive relationship with a very strong level of relationship.